Deus para mim é Odin: o paganismo nórdico contemporâneo no Brasil - Tsugami, Susan Sanae (2019)
Contemporary Norse Paganism is a broad religious category in which are included many different religious segments that aim to recover, reconstruct and re-signify Norse pre-Christian religion in the contemporary world. The interest in (Neo) Pagan religious movements is a worldwide phenomenon, making it possible to notice the manifestations of its countless segments in diverse locations, including Brazil. Among these many segments of (Neo) Paganism, we come across, for instance, Asatrú, Heathen and Forn Sidr. The followers of such religions use historical and literary sources in search of possible ways to systematize Scandinavian and Germanic pagan religions. This gives rise to many observations and broad discussions regarding the systematizations the believers tend to form as a result of their beliefs and religious discourses, which can be noticed, for example, in their search for the original pagan religion, resulting in a variety of problems involving discourses of purity. Therefore, academic debates are raised about these identifications, ideological thoughts and nationalist feelings on the believers’ part. In their attempt to legitimatise and authenticate their beliefs, the followers of Norse (Neo) Paganism claim their religious identities by making use of both academic and esoteric knowledges. A consequence of this is the dissemination of knowledge about runes, mythologies, ancestry and the practice of rituals named blót and sumble. The rituals, then, are understood to be central practices of Contemporary Norse Paganism. The present study proposes to investigate this religious movement in Brazil through field research of ethnographical character, to better understand the various practices and rituals, and reach an approximation of the re-signification processes the believers make regarding Norse mythology. The main method of data gathering for this study was participative observation, alongside interviews and photos, which are presented in order to illustrate the discourses and meanings around the religious elements as they pertain to the research’s participants.